ENGAGEMENT SOCIAL INTERACTION AND SURVIVAL STRATEGIES OF TRADITIONAL MARKET TRADERS IN ADDRESSING MODERN MARKET COMPETITORS - Siti Rahmah Tumanggor; Miftahul Jannah Tanjung; Titin Efrida Hasibuan; Mhd. Luthfi Daulay (Academic Solution Publisher, 2024)
This research discusses survival strategies and the influence of social interaction on traders at the Pasar Traditional Sukaramai, Medan. Using the qualitative method of descriptive analysis, the data collection technique in this research is interviews and observations carried out directly in the field. This research focuses on basic food traders in Pasar Sukaramai Medan and also consumers who are making transactions there. The results of this research show several survival strategies used by traders in traditional markets, including reducing prices and establishing good relationships with buyers. Social interactions also influence traders' survival strategies significantly.